A Review of Mechanism of Action of Moringa oleifera as an Inhibitor of Adipogenesis in Obesity - Gigih Andy Putra, Achmad; Louisa, Melva (Brawijaya University, 2023)
Background: Obesity has been becoming a global health problem that could cause the emergence ofmany other diseases. Several strategies are used to treat obesity, including lifestyle modifications,anti-obesity medications (pharmacotherapy), bariatric surgery, and gut microbiota transplantation.Pharmacotherapy is an effective treatment method and is often chosen by obese people because it isquite simple and does not require invasive and expensive procedures. However, long-term usage ofconventional medicines causes serious side effects. Therefore, studies about herbal medicineincreased significantly, one of them is Moringa oleifera (MO). Objectives: This review providesinformation about the pathways involved in the adipogenesis processes in obesity and how MO caninhibit adipogenesis through several pathways. Methods: Data were collected from PubMed based onthe keywords “moringa”, “obese”, “adipogenesis”, “adipocyte”, and “lipogenesis”. There were 16journals in full text that met the inclusion criteria for conducting a literature study related to thesekeywords over the last 10 years (from 2013 to 2023). Results: The anti-obesity effect of MO isthought to come from several specific compounds isolated from this plant, including quercetin,isoquercetin, quercetin-3-O-malonylglucoside, astragalin, kaempferol, isothiocyanate, EGCG, andmany others. These active compounds can be isolated from various parts of the MO plant, but themost widely used are the leaves and seeds. These compounds exert anti-obesity activity by inhibitingadipogenesis through multiple pathways, including the AMPK, PI3K/AKT, MAPK, JAK/STAT,TGF-β, and Wnt/β-catenin pathways. Conclusions: Several in vivo, in vitro, and clinical trial studieshave been conducted to demonstrate the benefits and safety of MO as a medicinal plant withpharmacological potential to inhibit adipogenesis in obesity.Keywords: moringa; adipogenesis; adipocyte; lipogenesis; obese